Pattern Recognition Based on YIQ Colour Space with Simulated Annealing Algorithm and Optoelectronic Joint Transform Correlation - Chen, Chulung (European Journal of Applied Sciences, 2016)
<!--[if gte mso 9]> <![endif]--><span style="font-size: 11.0pt; mso-bidi-font-size: 12.0pt; line-height: 115%; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">For pattern recognition on various views of the interested colour object, we adopt the YIQ colour space when using simulated annealing algorithm to design the template matching function. Joint transform correlation is devoted for recognition of colour targets. Quantized reference functions are designed for the purpose of display on liquid crystal spatial light modulators. <span style="font-size: 11.0pt; mso-bidi-font-size: 12.0pt; line-height: 115%; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Each reference function is trained with true class images rotated in-plane at 2 degrees intervals between -14 degrees and 14 degrees. Numerical result shows that, generally, YIQ space outperforms conventional RGB space.<!--[if gte mso 9]> Normal 0 0 2 false false false EN-US ZH-TW X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->